Burnout Akademik di Era Digital: Studi Tentang Peran Manajemen Stres Dan Dukungan Institusi Pada Mahasiswa - S. Sinon, Iriwi Louisa; Arifin, Imran; Juharyanto, Juharyanto; Siboro, Asihora (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to analyze the extent to which stress management and institutional support influence academic burnout among university students in the digital era. Burnout refers to a state of chronic physical and emotional exhaustion, often accompanied by feelings of cynicism and detachment from academic pursuits. The occurrence of student burnout is closely related to prolonged and excessive stress resulting from the combination of increased academic workload, scholastic demands, depleted energy levels, diminished enthusiasm for academic tasks, lack of positive attitudes, and lower academic achievement. This research employs a quantitative approach using a survey method. Data were collected through questionnaires from 74 students across various study programs at the University of Papua. The data collection instrument consisted of a closed-ended questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression with the aid of SPSS version 25. The results indicate that stress management and institutional support have a significant negative effect on academic burnout. Together, these two variables explain 71.2% of the variability in burnout. These findings highlight the importance of enhancing individual capacity in managing stress and the active role of institutions in supporting students’ mental health amid the challenges of digital learning. Keywords: Academic Burnout; Digital Era; Stress Management; Institutional Support Abstrak: Penelitian ini bertujuan untuk menganalisis sejauh mana manajemen stres dan dukungan institusi berpengaruh terhadap burnout akademik mahasiswa di era digital. Burnout adalah keadaan kelelahan fisik dan emosional kronis, sering disertai dengan perasaan sinisme dan detasemen dari pengejaran akademik. Sementara itu, timbulnya kelelahan pada siswa terkait erat dengan stres yang berkepanjangan dan berlebihan yang timbul dari kombinasi meningkatnya pekerjaan akademik, tuntutan skolastik, tingkat energi yang menipis, berkurangnya antusiasme untuk tugas -tugas akademik, kurangnya sikap positif, dan pencapaian akademik yang lebih rendah. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei. Data dikumpulkan melalui kuesioner dari 74 mahasiswa berbagai program studi di Universitas Papua. Instrumen pengumpulan data berupa kuesioner tertutup yang telah diuji validitas dan uji reliabilitas. Analisis data menggunakan regresi linier berganda dengan bantuan SPSS 25. Hasil penelitian menunjukkan bahwa manajemen stres dan dukungan institusi berpengaruh negatif signifikan terhadap burnout akademik. Kedua variabel tersebut secara simultan menjelaskan 71,2% variabilitas burnout. Temuan ini menunjukkan pentingnya peningkatan kapasitas individu dalam mengelola stres serta peran aktif institusi dalam mendukung kesehatan mental mahasiswa di tengah tantangan pembelajaran digital. Kata kunci: Burnout Akademik, Era Digital, Manajemen Stres, Dukungan Institusi